Redesign, analysis, fabrication and testing of light weight fuselage, boom and empennage for solar UAV : part 1 - Yap, Kelvin Bing Hui (2014)
In recent years, a lot of research efforts have been put into Unmanned Aerial Vehicle (UAV) due to its ability to perform a wide variety of missions which include surveillance and recon, search and rescue operations, transport operations and other special operations deemed too dangerous or unsuitable for manned aerial vehicle. The Solar UAV Project is one such research project involving Final Year Aerospace Engineering students from Nanyang Technological University (NTU) and the Defence Science Oganisation (DSO) National Laboratories. This project aims to design and build a High Altitude and Long Endurance (HALE) UAV powered by solar energy. Entering the 3rd year of the project, the author will continue the work of his predecessors and focus his efforts on the design and structural analysis of the empennage section. In this report, the author will first detail the design process he has undergone, following an evaluation of the design done in the previous year. After a series of design re-iterations, the author arrived at 2 empennage configurations for the final considerations. Based on the design criteria set up by the mission requirements, the author will then evaluate his designs to determine which configuration will be used for the Solar UAV. This evaluation will include the weight trade-off analysis for the empennage section and the structural analysis of the critical members in the empennage. In addition, the author will also detail the experiment process he had undergone with the test spar manufactured in order to obtain important material properties which will be useful for subsequent phases of the project. Future work for this portion of the project includes finalized engineering drawings required for the production of the empennage section and an in-depth structural analysis and optimization of the components.